PTU-270 Single centre analysis of the cause of death following colorectal surgery. (22nd June 2015) - Macrow, C; Vallance, A; Burke, D
Abstract : Introduction: Publication of performance data for surgeons has recently been introduced in an attempt to improve quality of healthcare. This has included national publication of mortality following colorectal surgery. However, it is unknown what proportion of deaths attributed to a surgeon is a result of the surgical approach, rather than a medical complication. Method: A single-institution quantitative retrospective audit of all post-operative cases of 30 day mortality following colorectal surgery, between the 18 month period of 1st May 2010 to 31st October 2011 was completed. Eight consultant surgeons contributed to the audit. The colorectal department's database of mortality cases was reviewed and the notes of all patients retrieved. These were examined and a cause of death, medical or surgical, was identified using the American College of Surgeons National Surgical Quality Improvement Program (NSQIP) dataset. Results: Ninety eight cases of death attributed to the surgical team were reviewed. Of these 42, (43%) did not undergo surgery and 12 notes had insufficient data. Of the 44 patients who had surgery and died, 13 deaths (30%) were classified as surgical, with the rest (70%) being medical. The commonest medical cause being exacerbation of a pre-operative medical condition (48%) e.g. chronic airways disease, followed by myocardial infarction and chest infection With regard to timing of surgery, 10 (56%) of 19 elective deaths were surgical, whereas 22 (83%) of 25 acute deaths were medical. Conclusion: These data demonstrate that surgical technique is not commonly the cause of death following colorectal surgery. The data suggest that directing the focus of care to improve the patient's perioperative medical condition, particularly in the acute setting, is likely to improve post-operative outcome. Disclosure of interest: None Declared.